Synthesis and characterization of novel olefin complexes of palladium(0) with chelating bis(N-heterocyclic carbenes) as spectator ligands. (1st November 2018) - Scattolin, T.; Canovese, L.; Visentin, F.; Santo, C.; Demitri, N.
Graphical abstract: Ten Pd(0) complexes stabilized by bis-carbene and electron-withdrawing olefin ligands were synthesized and characterized. It was shown that the less efficient deactivated olefin capable of stabilizing the complexes bearing strong σ-donating bis-carbene species was dimethylfumarate. Abstract: We have synthesized several novel palladium(0) olefin complexes stabilized by strong σ-donating bis-chelating carbene ligands characterized by one or two CH2 spacers and electron-withdrawing olefins. Although it appears obvious that the σ-donating carbenes and electron-withdrawing olefins should cooperate in the stabilization of the ensuing complexes, the limit of their coexistence was not hitherto clear. On the basis of previously measured stabilizing capability of the olefins toward Pd(0) complexes we were able to synthesize ten complexes (nine new and one synthesized by a different protocol from that of the literature). The less electron-withdrawing olefin capable of stabilizing the complex was dimethylfumarate. However, the most interesting results were obtained with the (Z)-1, 2-bis(p-tolylsulfonyl)ethene ( cis -sulf) which instantly isomerizes upon coordination and in the case of the derivative bearing the olefin tetramethyl ethene-1, 1, 2, 2-tetracarboxylate (tmetc) whose decomposition in CD2 Cl2 yields the saturated tetramethyl ethane-1, 1, 2, 2-tetracarboxylate (D2 ). The solid-state structure of the complex4d bearing the bis-carbene 1, 1′-dibenzyl-3, 3′methylenediimidazol-2, 2′-diylidene and the olefin (E)-1, 2-bis(p-tolylsulfonyl)ethene ( trans -sulf) was also determined.